Mode-locked 2μm fiber laser with a multi-walled carbon nanotube as a saturable absorber - Azooz, Salam . M; F. Ahmad, F. Ahmad; Ahmad, Harith; Harun, Sulaiman . Wade.; Hamida, Belal Ahmed; Khan, Sheroz; A. Halder, A. Halder; M. C. Paul , M. C. Paul; M. Pal, M. Pal; S. K. Bhadra, S. K. Bhadra (Chinese Optics Letters, 2015)
We propose and demonstrate a passively mode-locked fiber laser operating at 1951.8 nm using a commercial thulium-doped fiber (TDF) laser, a homemade double-clad thulium–ytterbium co-doped fiber (TYDF) as the gain media, and a multi-walled carbon nanotube (MWCNT) based saturable absorber (SA). We prepare the MWCNT composite by mixing a homogeneous solution of MWCNTs with a diluted polyvinyl alcohol (PVA) polymer solution and then drying it at room temperature to form a film. The film is placed between two fiber connectors as a SA before it is integrated into a laser ring cavity. The cavity consists of a 2 m long TDF pumped by a 800 nm laser diode and a 15 m long homemade TYDF pumped by a 905 nm multimode laser diode. A stable mode-locking pulse with a repetition rate of 34.6 MHz and a pulse width of 10.79 ps is obtained when the 905 nm multimode pump power reaches 1.8–2.2 W, while the single-mode 800 nm pump power is fixed at 141.5 mW at all times. To the best of our knowledge, this is the first reported mode-locked fiber laser using a MWCNT-based SA.